Exploring the Dependency of Teachers and Students Regarding the Use of Guidebook in Bangladesh - Hossain, Md. Imran; Hossain, Md. Shahadat; Aich, Arnima (Advances in Social Sciences Research Journal, 2025)
Guidebooks are quite popular in Bangladesh. There are currently more guidebooks than literary works on the shelves of libraries. It is worthwhile to analyse the popularity of guidebooks because it is indicative of the education system in Bangladesh. This study seeks to shed light on the utilization and reliance on guidebooks by students and teachers in Bangladesh, as well as the causes and consequences of this reliance. This is qualitative research that focuses on a full understanding and analysis of the topic of educational guidebooks in Bangladesh. Teachers and students have been interviewed for this purpose. This has allowed for a comprehensive understanding of the inner workings of our nation's education system. The study's principal findings demonstrate that teachers and students are highly dependent on guidebooks because of majority of the teachers are untrained and lack of degrees in the subjects they teach, the ineffectiveness of NCTB textbooks, lot of pressure from the school administration, guidebook language is easier, organized and translations are offered. In addition, students are encouraged to use guidebooks because of their tendency of memorizing, better practicing opportunities and help to achieving good marks in the examination. The study recommended that the state must create a policy that formally recognises and enhances textbooks involvements of the teachers and students.